Commemorating 10 years IAMB. In the Volksgebouw. Place of persons indicated on the back. From: De Wapens Neder, august 1931
Commemorating 10 years IAMB. In the Volksgebouw. Place of persons indicated on the back. From: De Wapens Neder, august 1931.